Pneumoperitoneum in the Newborn: Is Surgical Intervention Always Indicated? - Rahul Gupta; Shyam Bihari Sharma; Priyanka Golash; Ritesh Yadav; Dhawal Gandhi (EL-Med-Pub, 2014)
Pneumoperitoneum in the neonate generally is an acute surgical emergency, which has grave implications, and immediate surgical intervention is needed to ensure survival. The most common cause is a perforated hollow viscus. However, there are causes that cannot be attributed to this etiology, constituting what has been called non-surgical, asymptomatic, benign, misleading, spontaneous or idiopathic pneumoperitoneum. Knowledge of this entity and its likely aetiological factors should improve awareness and possibly reduce the imperative to perform an unnecessary emergency laparotomy on an otherwise normal neonate with an unexplained pneumoperitoneum.